Marketing Mix-Based Business Development Strategy For Priti Batik Msmes In Jember Regency - Erik Duwi Saputri; Budi Santoso; Yohanes Gunawan Wibowo (Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the implementation of marketing mix strategies (product, price, promotion, place), examine their influence on business performance, and identify their role in the development of SMEs, specifically Priti's Batik and Batik Sekar Arum in Jember Regency. This research employs a qualitative approach using thematic analysis method. Data were collected through in-depth interviews, observation, and documentation involving business owners as key informants. The results show that the marketing mix strategy implementation in both SMEs has been conducted but is not yet optimal. In terms of product, both businesses have strengths in quality and distinctive local motifs; however, innovation and brand identity development remain limited. Regarding pricing, strategies are primarily cost-based and adjusted to product quality. In promotion, digital media utilization is still not maximized, with marketing activities largely relying on direct selling and personal networks. In distribution, both SMEs mainly utilize direct channels with limited market reach. The marketing mix strategy significantly influences SME performance, particularly in increasing sales, expanding market reach, and strengthening customer relationships. The integrated marketing mix implementation also supports business development through product innovation, digital marketing utilization, and distribution channel expansion. This research is expected to serve as a reference for SME practitioners in formulating more effective marketing strategies. This study contributes by providing empirical insights into the application of marketing mix strategies in batik SMEs and their impact on business performance and development. It is expected to serve as a reference for SME practitioners in formulating more effective marketing strategies and for future researchers in expanding studies on SME marketing.